New-age vaccine adjuvants, their development, and future perspective - Verma, Shailendra Kumar; Mahajan, Pooja; Singh, Nikhlesh K.; Gupta, Ankit; Aggarwal, Rupesh; Rappuoli, Rino; Johri, Atul Kumar (Frontiers in Immunology, 2023)
In the present scenario, immunization is utmost needed method to keep human beings safe and healthy from the notorious and infectious agents. Despite the great success in the field of vaccinology, there is not only the requirement for developing safe and ideal vaccines to counteract the deadly infections but also to improve the quality of already developed vaccines in terms of partial or inconsistent protection. Generally, subunit vaccines are known to be safe in nature, but they are mostly found incapable to generate the optimum immune response. Hence, there is a great possibility to improve the potential of a vaccine in formulation with novel adjuvants, which can effectively impart the superior immunity. The vaccine/s in formulation with novel adjuvants may also be helpful to encounter the pathogens of high antigenic diversity. However, due to the limitations of safety and toxicity, very few human compatible adjuvants have been approved. In this review, we mainly focus on the necessity of new and improved vaccines; definition and need of adjuvants, the characteristics and mechanisms of human compatible adjuvants, current status of vaccine adjuvants, mucosal vaccine adjuvant, adjuvants in clinical development, future directions and conclusion.